Introduction to Renewable Energy Powered Desalination - Kalogirou, Soteris A. (My University, 2018)
Life on earth depends on water, which is an essential element for life. Three-fourths of the planet's surface is covered with water but 97% of this huge quantity is contained in the oceans and is salty water and only a tiny 3% is freshwater. This small percentage of the earth's water, however, supplies most of the needs of humanity and exists in lakes, rivers, and ground water. As can be understood, the only practically inexhaustible sources of water are the oceans, which, however, are of very high salinity, much above the safe consumption limit. It would be therefore possible to address the water shortage problem faced by many countries and many millions of people with seawater desalination. The separation of salts from seawater, however, requires large amounts of energy which, when produced from fossil fuels, can increase the environmental pollution and thus the climate problems of the earth. There is therefore a need to employ environmental-friendly energy sources, such as renewables, in order to desalinate seawater. A large variety of systems used to convert seawater into freshwater suitable for human use are presented in this chapter together with a variety of systems which can be used to convert effectively renewable energy sources into useful forms of energy. These can be used to power desalination systems and include solar collectors, photovoltaics, solar ponds, and geothermal energy. Both direct and indirect collection systems are presented. Direct collection systems use one piece of equipment both to collect solar radiation and use the energy collected to desalinate seawater. The representative example of these types of systems is the solar still. In contrast, indirect collection systems employ two different subsystems: one for collecting renewable energy and a different one for desalination. These comprise two broad categories: the phase change processes, which include the multistage flash, multiple effect distillation, vapor compression, and membrane distillation; and the membrane processes, which include reverse osmosis and electrodialysis. The chapter concludes with some general guidelines which can be used for the selection of desalination and renewable energy systems, their combination to produce freshwater in an environmental-friendly way, and the parameters that need to be considered.
Keywords: Electrodialysis; Multiple effect; Multistage flash; Reverse osmosis; Solar desalination; Solar stills